Testing of antiplasmodium activity substance from endophytic fungus of Artemisia annua L. - ., Wahyono; ., Pudjono; P., Widyati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Malaria is a life-threatening disease caused by Plasmodium parasites. The rapid spread of malaria-quinoline resistance enforce to find of new antimalaria drug. Artemisia annua L having artemisinin as secondary metabolites, has been used as antimalaria agent for long time. One of source of bioactive compound is endophytic fungus. This fungus can produce similar bioactive compound to host plant. The thin layer chromatography result showed that endophytic fungusfrom A.annua had similar chromatogram profile with artemisinin. This metabolite was not secreted in the fermentation medium, but was kept in the fungus mycelium. The result of the haem polymerization inhibitory activity assay showed that this secondary metabolites inhibited the haem polymerization. Ethyl acetate extract of fungus A had IC50 value 0.824 ± 2.89 μM to inhibit the haem polymerization; fungus E was 0.861± 2.43 μM; and fungus F was 1.394 ± 3.73 μM.Key words : endophytic fungus, antiplasmodium, the haem polymerization, IC50